2018
DOI: 10.1111/jbi.13155
|View full text |Cite
|
Sign up to set email alerts
|

Parallel bursts of recent and rapid radiation in the Mediterranean and Eritreo‐Arabian biodiversity hotspots as revealed byGlobulariaandCampylanthus(Plantaginaceae)

Abstract: Aim Molecular phylogenetic inferences have been important to test hypotheses of the temporal and geographical origin of plant lineages from the Mediterranean region (MR) and their rates of diversification. However, comparisons are still rare between well‐sampled and closely related clades from within and outside the MR. Here, we compare the biogeographical histories and diversification rates between two main genera of woody perennial Plantaginaceae with highest species diversities in the MR (Globularia) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 77 publications
(106 reference statements)
1
25
0
Order By: Relevance
“…Evidence from recent molecular data support the hypothesis that G. section Empetron is one of the latest branching lineages in the evolution of Globularia, and that G. meridionalis, G. cordifolia, and G. neapolitana are close to G. repens [1,5]. According to Milletti [6], such large variability could be explained by the wide area of occurrence of the species and their habitat fragmentation, noting a large polymorphism and quoting Willkomm [32] for the explanation, "Hic speciei typus per innumeras formas intermedias transit in varietatem" (English: "This type of species passes from variety to variety through countless intermediate forms").…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence from recent molecular data support the hypothesis that G. section Empetron is one of the latest branching lineages in the evolution of Globularia, and that G. meridionalis, G. cordifolia, and G. neapolitana are close to G. repens [1,5]. According to Milletti [6], such large variability could be explained by the wide area of occurrence of the species and their habitat fragmentation, noting a large polymorphism and quoting Willkomm [32] for the explanation, "Hic speciei typus per innumeras formas intermedias transit in varietatem" (English: "This type of species passes from variety to variety through countless intermediate forms").…”
Section: Introductionmentioning
confidence: 99%
“…The number of species belonging to this genus and their taxonomic status have been interpreted in several ways by the authors who have studied these plants over the years. Currently, 27 taxa are included in this genus [5], of which many are narrow endemics [1, 6,7]. Recent molecular studies have demonstrated that Globularia, which was traditionally included in a separate family (Globulariaceae) along with Poskea Vatke, actually belongs to Plantaginaceae [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations